Surplus federal computers for schools : an assessment of the early implementation of E.O. 12999 - Glennan, Thomas Keith, 1935-; Baer, Walter S.; Purnell, S. W.; Farnsworth, Gwen.; Schuyler, Gina L.; Rand eBooks (Santa Monica, CA : RAND, 1997)
In April 1996, President Clinton signed an executive order (E.O.) intended to promote transfer of unneeded federal government computer equipment to schools and educational nonprofit organizations. The federal government owns about 2 million personal computers, and approximately 100,000 operable computers become surplus each year. In the first year of implementation, 30,000 to 50,000 computers were donated to schools, many of which were not in operating condition. Private-sector experience suggests that use of specialized organizations to upgrade and refurbish computers can increase the number of operable and useful computers substantially. About 60 agencies have developed implementation plans, some of which build on existing programs. Agencies with the most computers are concerned with how the E.O. will affect existing programs. Almost all program leaders feel that the program is not a high priority at upper agency levels, especially since no funds are authorized for carrying out the order. Concerns also exist about identifying appropriate recipients, delivery to recipients, and how to upgrade and repair equipment. To address all these concerns, the authors draw on the successful donation experiences of established federal programs and the public sector to make recommendations for continuing implementation.
"Critical Technologies Institute."
Includes bibliographical references.
Also available on the internet via WWW in PDF format.
Keywords: Computers -- United States; Education -- United States -- Data processing; Educational technology -- United States; Federal aid to education -- United States; Schools -- United States -- Furniture, equipment, etc; Surplus government property -- United States; Electronic books